(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
In recent years, a lot of research is being carried out in various areas of linguistics, which is the reason for the discovery of unknown aspects in the field. Also, the sociolinguistic terminology is enriched with many examples. In this article, the important lexical- semantic features of prison slang are tried to be revealed more through examples.